Nysa-Scythopolis: The Hellenistic Polis - Mazor, Gabriel; Atrash, Walid (Journal of Hellenistic Pottery and Material Culture, 2017)
For ninety-five years excavations have been going on at the site of Hellenistic Nysa-Scythopolis. From 1921 to 1923 the expedition of the Pennsylvania University Museum, Philadelphia worked at Tel Bet She’an. From 1991 to 1994 and 2005 to 2010 the expeditions of the Bet She’an Archaeological Project and the Israel Antiquities Authority were active at Tel Bet She’an and Tel Iẓtabba, sites located on both banks of Nahal Ḥarod (ﬁg. 1). The excavations revealed the construction of a military stronghold and an administrative centre of the mid-3rd century BCE on Tel Bet She’an and the foundation of a polis on Tel Iẓtabba around 170 BCE until the destruction of Hellenistic Nysa-Scythopolis by the Hasmoneans in 108 / 107 BCE. Numerous scholars published their research on the material culture and ancient sources, highlighting the history and cultural identity of Nysa-Scythopolis, a Greek city of Coele Syria. This article summarizes the basic data of those researches and reviews the archaeological and historical evidence.